"Being on the Other Side of the Table": A Qualitative Study of a Community-Based Science Learning Program With Latinx Families. (April 2023) - Kirmaci, Mehtap; Buxton, Cory A.; Allexsaht-Snider, Martha
Building upon a Freirean notion of dialogic education, the purpose of this multi-case study was to explore what happened when secondary science teachers came together with Latinx parents for their children's science learning in the context of a community-based science learning program. Constant comparative analysis of data revealed similarities and differences among the cases that were analyzed in three categories: recognition, adaptation, and pro-action. Implications are that in-depth exposure to content-based cultural immersion programs with parents can be beneficial for teachers to cultivate a broader vision of science (and other content area) teaching linked to students' lives and communities.